Osteoid cell-derived chemokines drive bone-metastatic prostate cancer - Catherine S. Johnson; Catherine S. Johnson; Leah M. Cook; Leah M. Cook (Frontiers in Oncology, 2023)
One of the greatest challenges in improving prostate cancer (PCa) survival is in designing new therapies to effectively target bone metastases. PCa regulation of the bone environment has been well characterized; however, bone-targeted therapies have little impact on patient survival, demonstrating a need for understanding the complexities of the tumor-bone environment. Many factors contribute to creating a favorable microenvironment for prostate tumors in bone, including cell signaling proteins produced by osteoid cells. Specifically, there has been extensive evidence from both past and recent studies that emphasize the importance of chemokine signaling in promoting PCa progression in the bone environment. Chemokine-focused strategies present promising therapeutic options for treating bone metastasis. These signaling pathways are complex, with many being produced by (and exerting effects on) a plethora of different cell types, including stromal and tumor cells of the prostate tumor-bone microenvironment. ​This review highlights an underappreciated molecular family that should be interrogated for treatment of bone metastatic prostate cancer (BM-PCa).